Die hard, with a vengeance [videorecording (DVD)] - McTiernan, John; Willis, Bruce, 1955-; Irons, Jeremy, 1948-; Jackson, Samuel L. (Twentieth Century Fox Home Entertainment, 2013)
A New York detective is the target of a psychopathic terrorist planning to blow up the city if he does not get what he wants.